1997
DOI: 10.1021/la9620115
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of Nanocrystalline ZnO Films by Bis(2,2‘-bipyridine)(2,2‘-bipyridine-4,4‘-dicarboxylic acid)ruthenium(II)

Abstract: Spectral sensitization of nanocrystalline ZnO films has been carried out with ruthenium complex, bis-(2,2′-bipyridine)(2,2′-bipyridine-4,4′-dicarboxylic acid) ruthenium(II) or (Ru(II)). An incident photon to current conversion efficiency (IPCE) of 14% has been obtained for unbiased ZnO/Ru(II) photoelectrochemical cells. This low IPCE has been attributed to the poor light harvesting efficiency (LHE) and charge collection (η c) efficiency. The weak interaction between Ru(II) and ZnO surface which results in poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 74 publications
5
93
1
3
Order By: Relevance
“…iv) Films fabricated from the material need to deliver the surface area multiplicity necessary for efficient light harvesting from a monolayer of surface adsorbed dye. Some examples that have been employed are ZnO, [117][118][119][120] SnO 2 [121,122] and SrTiO 3 . [123] It has been found that the electron transport properties of DSCs fabricated using ZnO sintered nanoparticles are similar to those of TiO 2 .…”
Section: Non-tio 2 Mesoporous Metal Oxide Electrodesmentioning
confidence: 99%
“…iv) Films fabricated from the material need to deliver the surface area multiplicity necessary for efficient light harvesting from a monolayer of surface adsorbed dye. Some examples that have been employed are ZnO, [117][118][119][120] SnO 2 [121,122] and SrTiO 3 . [123] It has been found that the electron transport properties of DSCs fabricated using ZnO sintered nanoparticles are similar to those of TiO 2 .…”
Section: Non-tio 2 Mesoporous Metal Oxide Electrodesmentioning
confidence: 99%
“…These mesoscopic films of metal oxide semiconductors provide a high surface area and porous structure. Such ZnO films have been extensively employed in the construction of dye-sensitized solar cells [44][45][46][47] Images C and D in Figure 5 show f-CNT-ZnO composite under two different magnifications. Two different type of ZnO attachment can be seen from the micrographs in Figure 5C and D. In the first case aggregated clusters of ZnO crowd around the f-CNT bundles (Fig.…”
Section: Assembly Of Cnt-zno Composite On Electrode Surfacesmentioning
confidence: 99%
“…As atividades de pesquisas relacionadas a esta área foram impulsionadas pela habilidade para controlar as propriedades dos materiais através do controle do tamanho das partículas. Este desenvolvimento pode resultar em novas tecnologias, inclusive conversão de energia [19][20][21][22][23] , armazenamento de dados em altíssima densidade 24 , diodos emissores de luz (LED) 25 e pigmentos especiais 26 .…”
Section: Introductionunclassified
“…As atividades de pesquisas relacionadas a esta área foram impulsionadas pela habilidade para controlar as propriedades dos materiais através do controle do tamanho das partículas. Este desenvolvimento pode resultar em novas tecnologias, inclusive conversão de energia [19][20][21][22][23] Neste trabalho apresenta-se uma abordagem inicial sobre materiais nanoestruturados, em especial o dióxido de estanho, envolvendo alguns aspectos básicos. Versa-se sobre a técnica de obtenção deste composto pelo método químico e o controle do crescimento de partículas através de uma solução sólida supersaturada.…”
unclassified